THE APPLICATION TO TRANSLATE INDONESIAN LANGUAGE TO BALINESE LANGUAGE BY USING RULE BASED METHOD. - Ni Gusti Ayu Made Cita Dewi (Universitas Pendidikan Ganesha, 2012)
This study aimed: (1) to design the application to translate Indonesian language to Balinese language by using rule based method. (2) to implement the application to translate Indonesian language to Balinese language by using rule based method. In the design and implementation, researcher used a rule based method that has 4 stages, there are: (1) Parsing Text, (2) Stemming, (3) Searching of the meaning word, and (4) Rule Matching. The input from this application is Indonesian language text, while the output is Balinese language text. The testing process used the blacx box testing (functionality) and the white box testing (conceptual / structural). The result of this study is Indonesian language to Balinese language translation application named “Translator Indo-Bali” which is implemented using the Delphi 7 programming language. Based on trial result, it is known that the “Translator Indo-Bali” has done the translation from Indonesian language to the Balinese language well. So it can be concluded that the “Translator Indo-Bali” can assist people in learning the Balinese language.